PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP KARAKTER KREATIF SISWA KELAS V SDN KEDOYA UTARA 04 - Fitria Rosmi; Fildza Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of learning modelsProject Based Learning(PJBL) on the creative character of fifth grade students at SDN Kedoya Utara 04. The background of the research is based on the low creative character of students caused by teacher-centered learning, lack of facilities, and less varied learning models. The PJBL model was chosen because it is considered capable of providing space for students to think creatively through real project-based activities. This research uses a quantitative approach with the methodQuasi Experimental Designand research designPosttest Only Control Group DesignThe research sample consisted of two classes, namely the experimental class using the PJBL model and the control class using the conventional method, each consisting of 30 students. The instrument used was a creative character questionnaire with 23 valid and reliable items. The results of data analysis using the testIndependent Sample T-Testshows that there is a significant difference between the creative character of students in the experimental class and the control class, with a significance value of 0.000 < 0.05 and a t-count value of 10.150 > t-table 2.001. The average (mean) value of creative character in the experimental class is 84.33, higher than the control class of 67.87. Thus, it can be concluded that the use of the modelProject Based Learning(PJBL) has a positive and significant effect on improving the creative character of fifth grade elementary school students.